Regulatory t cells in immune response to infection - G. F. Zheleznikova (Журнал инфектологии)
The revue includes the contemporary information about regulatory T cells (Treg), that regulate the inflammatory responses and adaptive immune response in defense against infection. The different populations of Treg are described, their activation mechanisms, and the mechanisms of influencing target cells. The double role of Treg in infection pathogenesis is emphasized.